PENGETAHUAN DAN PERAN ORANG TUA DALAM PENCEGAHAN MALARIA PADA ANAK DI RUANG ANGGREK RUMAH SAKIT UMUM WAINGAPU - I GEDE ARIYAWAN; MARTHA METI KODY (Poltekkes Kemenkes Kupang, 2017)
Introduction:Malaria is an acute or chronic disease caused by protozoa of the genus of plasmodium characterized by fever, anemia and splenomegaly. The purpose of the study to know the description of knowledge and the old role in the prevention of malaria in children in the orchid room of the Umbu Rara Meha General Hospital. Method: The design of quantitative descriptive research with case study method. This sampling technique is non-random sampling (Non Probability Sampling). Sampling method in this research use accidental sampling technique. Result: From the result of the research, it is found that from 30 respondents who have good knowledge that is 11 people (37%), and the smallest respondent is the respondent with less knowledge that is 9 people (30%). For the role can be seen that the most respondents are respondents with good roles of 15 people (50%), and the smallest respondent is the respondent with a sufficient role of 5 people (17%). Conclusion: In conclusion, the knowledge and role of parents in preventing malaria in children in Orchid Room of Umbu Rara Meha General Hospital has been classified as good, this is due to the respondent's education factor that is already quite high and the age factor that has passed the process of good mental development. Suggestions for respondents are expected to increase the knowledge of respondents to know and do prevention against malaria in children.